The Button Connection – Embedding quotations. (1st June 2013) - Gröppel-Wegener, Alke
A short addendum to Pat Francis' report on her button activity – which it was inspired by – this contribution demonstrates how visual analogies can be used to help students visualize 'hidden' academic practice. Addressing students, it specifically uses the button to explain the concept of embedding quotations.